2016
DOI: 10.1116/1.4941069
|View full text |Cite
|
Sign up to set email alerts
|

Ion energy distribution function measurements by laser-induced fluorescence in a dual radio frequency sheath

Abstract: Ion dynamics are investigated in a dual frequency radio frequency sheath as a function of radius above a 30 cm diameter biased silicon wafer in an industrial inductively coupled (440 kHz, 500 W) plasma etch tool. Ion velocity distribution (IVD) function measurements in the argon plasma are taken using laser induced fluorescence. Planar sheets of laser light enter the chamber both parallel and perpendicular to the surface of the wafer in order to measure both parallel and perpendicular IVDs at thousands of spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…[46][47][48][49][50][51][52] To understand the dynamic behaviors of ions in plasmas, time-resolved LIF systems have been developed and applied to diagnose spatiotemporal fluctuations in plasma thrusters, [53][54][55][56][57] the temporal evolution of discharge and afterglow phases in pulsed plasmas, 58,59 and ion sheaths formed on AC-biased electrodes. [60][61][62][63][64][65] Time-resolved LIF measurements of ion sheaths were achieved by using pulsed dye lasers as the excitation-laser source and controlling the laser-pulse timing synchronized with the AC bias voltage applied to the electrode. To accurately evaluate the effects of tailored-waveform AC voltages on the IVDF, the temporal change in the IVDFs must be measured with sufficient data-acquisition timing in one cycle.…”
Section: Articlementioning
confidence: 99%
“…[46][47][48][49][50][51][52] To understand the dynamic behaviors of ions in plasmas, time-resolved LIF systems have been developed and applied to diagnose spatiotemporal fluctuations in plasma thrusters, [53][54][55][56][57] the temporal evolution of discharge and afterglow phases in pulsed plasmas, 58,59 and ion sheaths formed on AC-biased electrodes. [60][61][62][63][64][65] Time-resolved LIF measurements of ion sheaths were achieved by using pulsed dye lasers as the excitation-laser source and controlling the laser-pulse timing synchronized with the AC bias voltage applied to the electrode. To accurately evaluate the effects of tailored-waveform AC voltages on the IVDF, the temporal change in the IVDFs must be measured with sufficient data-acquisition timing in one cycle.…”
Section: Articlementioning
confidence: 99%
“…Durot et al also demonstrated a transfer function averaging technique via band-pass filtering, phase-sensitive detection and transfer function averaging [83]. A pulsed laser, generally with a low repetition rate, can perform time-resolved measurements by phrase-locking the laser pulse trigger with the temporal phenomena if such phenomenon is repeatable [30]. A similar procedure can be used with CW lasers via AOM modulation [40].…”
Section: Time Resolved and Perturbation Measurementsmentioning
confidence: 99%
“…It can be used to monitor the 2D IVDF distribution via planar LIF with a sheet of laser light. LIF has been used to measure ion properties within DC and RF sheaths in ICP devices, as described by Moore et al for a dual frequency (2.2 and 19 MHz) RF sheath [30]. Sadeghi et al also reported direct measurement of the argon ions and neutral VDFs in an ICP [163,164].…”
Section: Plasma Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…2005), plasma processing (Zimmerman, Mcwilliams & Edrich 2005; Jacobs et al . 2007; Moore, Gekelman & Pribyl 2016), and basic plasma physics (Lee et al . 2006; Lee, Hershkowitz & Severn 2007 a ; Lee, Oksuz & Hershkowitz 2007 b ; Yip, Hershkowitz & Severn 2010; Yip et al .…”
Section: Introductionmentioning
confidence: 99%